A dual osteoconductive-osteoprotective implantable device for vertical alveolar ridge augmentation - Dairaghi, Jacob; Benito Alston, Claudia; Cadle, Rachel; Rogozea, Dan; Solorio, Luis; Barco, Clark T.; Moldovan, Nicanor I. (Frontiers in Dental Medicine, 2023)
Repair of large oral bone defects such as vertical alveolar ridge augmentation could benefit from the rapidly developing additive manufacturing technology used to create personalized osteoconductive devices made from porous tricalcium phosphate/hydroxyapatite (TCP/HA)-based bioceramics. These devices can be also used as hydrogel carriers to improve their osteogenic potential. However, the TCP/HA constructs are prone to brittle fracture, therefore their use in clinical situations is difficult. As a solution, we propose the protection of this osteoconductive multi-material (herein called “core”) with a shape-matched “cover” made from biocompatible poly-ɛ-caprolactone (PCL), which is a ductile, and thus more resistant polymeric material. In this report, we present a workflow starting from patient-specific medical scans in Digital Imaging and Communications in Medicine (DICOM) format files, up to the design and 3D printing of a hydrogel-loaded porous TCP/HA core and of its corresponding PCL cover. This cover could also facilitate the anchoring of the device to the patient's defect site via fixing screws. The large, linearly aligned pores in the TCP/HA bioceramic core, their sizes, and their filling with an alginate hydrogel were analyzed by micro-CT. Moreover, we created a finite element analysis (FEA) model of this dual-function device, which permits the simulation of its mechanical behavior in various anticipated clinical situations, as well as optimization before surgery. In conclusion, we designed and 3D-printed a novel, structurally complex multi-material osteoconductive-osteoprotective device with anticipated mechanical properties suitable for large-defect oral bone regeneration.